KOMUNIKASI SIMBOLIK : PADA ATRAKSI BAMBU GILA DI NEGERI MORELLA DAN NEGERI SULI (DALAM PERSPEKTIF ETNOGRAFI KOMUNIKASI) - Demsy Wattimena; Junus Kwelju; Anthonio Latuihamallo; Maria Matatula (JURNAL BADATI, 2024)
Symbolic Communication of the Crazy Bamboo Attraction in a Communication Ethnography Perspective. This research uses qualitative research methods with an ethnographic communication approach. Ethnography aims to discover the essence and complexity of culture that can describe a community. The results of the research obtained. The crazy bamboo attraction is a typical culture of the people of Maluku which is full of mystical nuances. This attraction has been passed down from generation to generation, and until now this attraction still exists even though its existence has begun to erode over time because not all countries/villages in Maluku still have this attraction. We can find many verbal and non-verbal symbols when we see the crazy bamboo attraction. The message from the crazy bamboo attraction is: The content of the message from the crazy bamboo attraction is: The spirit of mutual cooperation in the lives of the people of Maluku, the spirit of togetherness that has been well maintained for the people of Maluku, disciplined obedience to what has been mutually determined to be universal noble values, There are values of mutual respect among the people of Maluku, maintaining the preservation of cultural heritage from generation to generation.